Yilmak Laundry Machine Maintenance Analysis with Reliability Centered Maintenance (RCM) and Risk Based Maintenance (RBM) Methods (Case Study: Laundry Department of PT. Eratex Djaja) - Roni Dwi Irawan (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
PT. Eratex Djaja is a garment company that produces products in the form of apparel. One of the parts in  production  is  the  Washing  section.  There  are  several  machines  in  the  washing  section,  including:  Tonello Machines,  Tolkar,  Yilmak,  Ramsons,  Belly.  The  problem  that  was  found  in  the  Washing  section  was  that  the Yilmak  Laundry  Machine  had  a  high  downtime  which  reached  9180  minutes.  This  study  aims  to  analyze  the system  on  these  machines  using  the  Reliability  Centered  Maintenance  (RCM)  and  Risk  Based  Maintenance (RBM)  methods.  From  the  analysis  of  the  RCM  method,  it  is  known  that  the  components  of  the  Motor  Drive, Pulley + V-belt, and shaft + Bushing are critical components. From the calculation of Total Minimum Downtime (TMD),  the  optimum  replacement interval for the  Motor  Drive component  is  25 days,  Pulley  +  V-belt 32 days, and  shaft  +  Bushing  30  days.  From  the  calculation  using  the  RBM  method,  the  value  of  risk  received  by  PT. Eratex Djaja if the Yilmak Laundry machine is damaged in the amount of Rp. 412,003,141.